(untitled) - David A. Warrell (Oxford ; New York, 2003)
Textbooks of medicine: raison d'etre Clinical medicine: changes, challenges, and reconsiderations Aculture ò public mistrust: the physician - patient relationship
Keywords: Internal medicine; Medicine